PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN PENDIDIKAN PANCASILA DENGAN MODEL KOOPERATIF TIPE INDEX CARD MATCH DI KELAS IV UPTD SDN 02 KOTO TUO KABUPATEN LIMA PULUH KOTA - Mahdiyah, Atikah; Waldi, Atri; Reinita; Erita, Yeni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low student learning outcomes in Pancasila Education Learning. This study aims to describe the improvement of student learning outcomes in Pancasila education learning using the cooperative model type index card match in Class IV UPTD SDN 02 Koto Tuo, Lima Puluh Kota Regency. The method used is Classroom Action Research (CAR), employing a qualitative and quantitative approach, conducted in 2 cycles, namely cycle I (2 meetings) and cycle II (1 meeting), carried out in four stages: planning, implementation, observation, and reflection. The subjects of this research are the teachers and students of class IV UPTD SDN 02 Koto Tuo, Lima Puluh Kota District, with a total of 20 students consisting of 10 boys and 10 girls. The results of the research conducted show that Pancasila Education learning using the Index Card Match cooperative model can improve students' learning outcomes in Pancasila Education in Class IV UPTD SDN 02 Koto Tuo, Lima Puluh Kota Regency).